Utilization and impacts of hydrogen in the ironmaking processes: A review from lab-scale basics to industrial practices. (29th July 2021) - Ma, Kaihui; Deng, Junyi; Wang, Gang; Zhou, Qi; Xu, Jian
Abstract: Hydrogen (H2 ) energy is a promising candidate to replace carbon monoxide (CO) as a reductant for iron oxide reduction in revolutionary ironmaking industrial processes, and numerous studies have been conducted to intensively study the utilization and impact of H2 in ironmaking processes. Therefore, this review first collects and compares the H2 -assisted reduction mechanism and kinetics. The impacts of H2 on the reduction accompanying behaviors, such as the disintegration, swelling, sticking, softening, and melting of iron ores, are then summarized. Third, the performance of H2 predicted by either mass and heat balance models or numerical simulation models in various ironmaking processes is highlighted. Finally, the different applications of hydrogen-rich materials in blast furnace and non-blast furnace ironmaking processes are further compared to illuminate H2 utilization before our outlook on the use of H2 in the ironmaking industry. Highlights: H2 has a great potential to replace fossil fuel used in ironmaking industry. H2 performs greater reduction rate than CO by reducing apparent activation energy. H2 reduces the disintegration, swelling, sticking of iron oxide, but delays its melting. H2 has lower utilization efficiency than CO in industrial practices. Mixing fossil fuel and H2 is suggested to be an efficient solution at present stage.